2020
DOI: 10.3390/cells9010255
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Keratinocytes on Sustained TGF-β Stimulation Reveal Partial EMT Features and Weaken Growth Arrest Responses

Abstract: Defects in wound closure can be related to the failure of keratinocytes to re-epithelize. Potential mechanisms driving this impairment comprise unbalanced cytokine signaling, including Transforming Growth Factor-β (TFG-β). Although the etiologies of chronic wound development are known, the relevant molecular events are poorly understood. This lack of insight is a consequence of ethical issues, which limit the available evidence to humans. In this work, we have used an in vitro model validated for the study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 90 publications
5
44
0
Order By: Relevance
“…Apart from that, GO:0042060 (wound healing) and GO:0043588 (skin development) have also been shown to enrich optimal genes associated with EMT. According to recent publications, both wound healing which involves cell–cell and cell-extracellular matrix interactions ( Kalluri, 2009 ; Yin et al, 2013 ) and skin development which associates with TGF-β signaling pathways ( Liarte et al, 2020 ) have been reported to be functionally related to the transformation between epithelial and mesenchymal cells ( Kalluri, 2009 ; Yin et al, 2013 ; Liarte et al, 2020 ), validating our prediction.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from that, GO:0042060 (wound healing) and GO:0043588 (skin development) have also been shown to enrich optimal genes associated with EMT. According to recent publications, both wound healing which involves cell–cell and cell-extracellular matrix interactions ( Kalluri, 2009 ; Yin et al, 2013 ) and skin development which associates with TGF-β signaling pathways ( Liarte et al, 2020 ) have been reported to be functionally related to the transformation between epithelial and mesenchymal cells ( Kalluri, 2009 ; Yin et al, 2013 ; Liarte et al, 2020 ), validating our prediction.…”
Section: Discussionsupporting
confidence: 87%
“…S8I-M ). IFEB received Tgfb1 and Tgfb2 (signals playing key roles in regulating epithelial-to-mesenchymal transition (EMT) for keratinocytes) from T cells, macrophages and germinative layer (GL) keratinocytes (55). Interactive plots for other types of cells were summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5,11,18 ] However, because HaCaT cells could express a large number of cell adhesion molecules (i.e., E‐cadherin) during the proliferation, which could form the adherens junctions to bind cells with each other, HaCaT cells tend to aggregate and appear clumped in Figure 2c, which is well consistent with the result of the previous report. [ 53 ] But just because of the confinement of the adhesion molecules, it makes the morphological variation of the HaCaT cells treated by CDots less obvious. Thus, HaCaT cells should be first digested by trypsin and then seeded into culture flasks for the detailed investigations of the morphological variation and the confirmation of EMT process.…”
Section: Resultsmentioning
confidence: 99%